E-modules in English for learners in Malasiqui II District - Morales, Merlinda S. (University of Pangasinan : [s.n.], 2020)
This study looked into the specific competencies in English where Grade 6 learners were weak at and utilized the Identified least-learned competencies to inform the development of a set of E-Modules. The descriptive-developmental and pre-experimental methods of research were used in this study. Main data- gathering tools were the teacher-developed and validated English tests administered to Grade 6 pupils before and after the implementation of the instructional Interventic using the E-Modules.
Bibliography: pages 129-135.
CHED-La Union
Keywords: Teaching -- Aids and devices